L‐Aspartate as a high‐quality nitrogen source in Escherichia coli: Regulation of L‐aspartase by the nitrogen regulatory system and interaction of L‐aspartase with GlnB. Issue 4 (3rd November 2020) - Schubert, Christopher; Zedler, Sandra; Strecker, Alexander; Unden, Gottfried
Abstract: Escherichia coli uses the C4‐dicarboxylate transporter DcuA for L‐aspartate/fumarate antiport, which results in the exploitation of L‐aspartate for fumarate respiration under anaerobic conditions and for nitrogen assimilation under aerobic and anaerobic conditions. L‐Aspartate represents a high‐quality nitrogen source for assimilation. Nitrogen assimilation from L‐aspartate required DcuA, and aspartase AspA to release ammonia. Ammonia is able to provide by established pathways the complete set of intracellular precursors (ammonia, L‐aspartate, L‐glutamate, and L‐glutamine) for synthesizing amino acids, nucleotides, and amino sugars. AspA was regulated by a central regulator of nitrogen metabolism, GlnB. GlnB interacted with AspA and stimulated its L‐aspartate deaminase activity (NH3 ‐forming), but not the reverse amination reaction. GlnB stimulation required 2‐oxoglutarate and ATP, or uridylylated GlnB‐UMP, consistent with the activation of nitrogen assimilation under nitrogen limitation. Binding to AspA was lost in the GlnB(Y51F) mutant of the uridylylation site. AspA, therefore, represents a new type of GlnB target that binds GlnB (with ATP and 2‐oxoglutarate), or GlnB‐UMP (with or without effectors), and both situations stimulate AspA deamination activity. Thus, AspA represents the central enzyme for nitrogen assimilation from L‐aspartate, and AspA is integrated into the nitrogen assimilation network by the regulator GlnB. Abstract : Escherichia coli uses L‐aspartate as a high‐quality source for nitrogen assimilation which required DcuA for uptake and aspartase AspA for ammonia release. AspA was regulated by a central regulator of nitrogen metabolism, GlnB. GlnB interacted with AspA and stimulated L‐aspartate deaminase activity (NH3 ‐forming). GlnB stimulation required 2‐oxoglutarate and ATP, or uridylylated GlnB‐UMP, consistent with the activation of nitrogen assimilation under nitrogen limitation. AspA therefore represents a new type of GlnB target that binds GlnB (with ATP and 2‐oxoglutarate), or GlnB‐UMP (with or without effectors) which stimulates AspA deamination activity.